Brazilian Paternity: survey of scientific production from 2003 to 2014 - Souza, José Neivaldo de; Negri, Matheus (Vox Scripturae - Revista Teológica Internacional, 2017)
The objective was to investigate and systematize the academic productions related to paternity in the Brazilian context published between 2003 and 2014. Identifying the theoretical academic production about paternity in the Brazilian context, found in electronic databases Lilacs (Latin American Literature and Caribbean Information Science in Health Sciences), Scielo (Sientifc Electronic Library Online) and BVS Ministry of Health (Virtual Health Library). The method used was the “state of the art” or “state of knowledge”. In this survey the descriptor, paternity, was used, reaching the general result of 1732 scientific studies. With the exclusion of duplicate articles, of those who escape the subject, highlighting the period determined for the research, the analysis was reduced to 102 scientific studies. Regarding the methodology, the papers were classified as theoretical, quantitative and qualitative studies. For the thematic analysis, the categories presented by Michel E. Lamb (2004) for the study of paternity: the nature of paternal involvement, the influence of paternity and determinants of paternal involvement were used. The thematic analysis included articles on the nature of parental involvement (43), the influence of paternity (18) and the determinants of paternal involvement (41). No concern had been identified in national scientific research about paternity and its relation to spirituality or religiosity. According to Juritsch (1970), the father has a special ability to bring the child to spiritual life, and in no way can he fail to pay attention to this point.
Keywords: Fatherhood; Parents; Family; Men